The Influence of Clinical Supervision on Teachers' Knowledge and Teaching Ability at SDN 7 Sungai Tohor Barat - Siti Mahot Hasibuan; Musnar Indra Daulay; Ramdhan Witarsa (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
This study aims to analyze the influence of clinical supervision on teachers' knowledge and teaching ability at SDN 7 Sungai Tohor Barat. The research method used is quantitative with a survey approach. The research sample consists of 10 teachers from SDN 7 Sungai Tohor Barat. Data was collected through questionnaires that measure teachers' knowledge and teaching ability before and after receiving clinical supervision. Data analysis was conducted using a t-test to determine significant differences before and after clinical supervision. The results of the study indicate a significant increase in teachers' knowledge and teaching ability after clinical supervision. Clinical supervision has proven effective in enhancing teachers' competence, both in terms of knowledge and teaching ability. The implication of this study is the importance of routine implementation of clinical supervision to improve the quality of teaching in elementary schools.